Doe guided chitosan based nano-ophthalmic preparation against fungal keratitis. (2021) - Hassan, Nazia; Mirza, Mohd Aamir; Aslam, Mohammed; Mahmood, Syed; Iqbal, Zeenat
Abstract: A recent upsurge in ocular infections is a pointer towards an enhanced prevalence of ophthalmic disorders, posing challenges for researchers globally. The caveats of conventional therapeutics demand a specifically designed Ocular Drug Delivery System (ODDS) and hence the primary objective of the present work is a fabrication of a Design of Expert (DoE) guided Chitosan based Antifungal loaded Nanoparticles (CANs), as a locoregionally effective eye formulation/drops for fungal keratitis therapy. The purported formulation was prepared using High-Pressure Homogenisation technique and was critically characterized on various parameters to check their suitability as an ODDS. The optimized formulation has fruitfully yielded irregularly spherical particles in up to a size of 200 nm and a Poly-dispersity Index (PDI) of less than 0.2 nm. The optimised formulation has further showcased a high mucoadhesion capacity thereby, suggesting the greater retention of CANs on the mucous membrane of an eye with low ocular irritancy as highlighted using HET-CAM (Hen's Egg Chorioallantoic Membrane) test. The in-vitro drug release study across a dialysis membrane has indicated both diffusion as swelling controlled release pattern for an optimized formulation. The ex-vivo corneal permeation study on goat corneal tissues using a Franz-Diffusion cell also has indicated a steady increase in the permeation of drug with time for an optimized formulation. Further, the optimised formulation was found to be non-irritant and ocular safe in ex-vivo transcorneal toxicity studies on goat corneal tissues. In conclusion, the designing of a proposed nanosized formulation, offers a promising step towards the management of external ocular diseases with a positive attributes of high patient compliance, controlled drug delivery, prolonged drug precorneal residence time and enhanced ocular bioavailability. The optimized CANs could be further exploited as a potential ODDS.